Circular RNAs: The Novel Actors in Pathophysiology of Spinal Cord Injury - Sámano, Cynthia; Mladinic, Miranda; Mazzone, Graciela L. (Frontiers in Integrative Neuroscience, 2021)
Spinal Cord Injury (SCI) can elicit a progressive loss of nerve cells promoting disability, morbidity, and even mortality. Despite different triggering mechanisms, a cascade of molecular events involving complex gene alterations and activation of the neuroimmune system influence either cell damage or repair. Effective therapies to avoid secondary mechanisms underlying SCI are still lacking. The recent progression in circular RNAs (circRNAs) research has drawn increasing attention and opened a new insight on SCI pathology. circRNAs differ from traditional linear RNAs and have emerged as the active elements to regulate gene expression as well as to facilitate the immune response involved in pathophysiology-related conditions. In this review, we focus on the impact and possible close relationship of circRNAs with pathophysiological mechanisms following SCI, where circRNAs could be the key transcriptional regulatory molecules to define neuronal death or survival. Advances in circRNAs research provide new insight on potential biomarkers and effective therapeutic targets for SCI patients.